2011
DOI: 10.1007/s11916-011-0240-0
|View full text |Cite
|
Sign up to set email alerts
|

Dependent Behavior in Patients with Medication-Overuse Headache

Abstract: Two thirds of patients with medication-overuse headache (MOH) fulfilled criteria for dependence on acute symptomatic treatments for pain, not exclusive of psychoactive medications, based on the fourth edition of the Diagnostic and Statistical Manual of Mental Disorders. Several questionnaires have been used to assess dependent behavior in patients with MOH. Findings regarding underlying psychological profiles of dependence and MOH are not consistent. Nevertheless, several neuroimaging, genetic, and neurobiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…Therefore, in our study, patients with unsuccessful outcome (NR-group) had, in some items, a LDQ subscore similar to that found in addicts in items assessing compulsive dependence according to DSM-IV criteria [18, 25, 29]. …”
Section: Discussionmentioning
confidence: 68%
“…Therefore, in our study, patients with unsuccessful outcome (NR-group) had, in some items, a LDQ subscore similar to that found in addicts in items assessing compulsive dependence according to DSM-IV criteria [18, 25, 29]. …”
Section: Discussionmentioning
confidence: 68%
“…Studies suggest that MOH represents a spectrum of addictive behaviors and some have shown a relation to characteristics of obsessive‐compulsive personality disorder . If MOH exemplifies a dependency‐like behavior, personality traits should differ as compared to migraine patients.…”
Section: Introductionmentioning
confidence: 99%
“…Medication abuse by headache patients may share pathogenic mechanisms and genetic factors with other types of drug through enhancement of predisposition factors [150][151][152]. In this sense, inhibition of histone deacetylase 3 seems to play a role in the memory processes involved in cessation of drug dependency in animal models [153].…”
Section: Medication Abusementioning
confidence: 99%